Using cluster analysis to regions grouping by the degree of investment appeal - Корепанов, Георгій Сергійович; Лазебник, Юлія Олександрівна; Пономарьова, Тетяна Володимирівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article is devoted problems of an estimation of investment appeal of territories. In the article it is offered to make grouping of regions by degree of investment appeal according to the claster analysis (with the regions of Iraq for example).